Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Luminescence chronology and sedimentology of the Maputaland barrier–dune complex (South Africa): new insights into MIS 5e dune construction and Late Holocene reactivation - Daria Semikolennykh; Alastair C. Cunningham; Aysylu Khisamutdinova; Anastasia Novikova; Simon J. Armitage; Mary Evans; Jasper Knight; Rachel Haupt; Axel Hofmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

Diversity of convolutid acoels (Convolutidae, Acoela) in Hokkaido, Japan, including a description of the symbiont-bearing Amphiscolops ranshimensis n. sp. - Siratee Riewluang; Regine C. Manglicmot; Shaun Cunningham; Matthew D. Hooge; Rintaro Ono; Hiroshi Kajihara; Brian S. Leander; Kevin C. Wakeman (Zoologischer Anzeiger, 2026)

Postnatal environment differentially modulates neurodevelopmental outcomes following voluntary prenatal oxycodone exposure in rats - Kelsea R. Gildawie; Kerri E. Budge; Sara B. Isgate; Jillian Celatka; Megan Gulsby; Cora C. Cunningham; Fair M. Vassoler; Elizabeth M. Byrnes (Neurotoxicology and Teratology, 2026)

Diversity and toxicity of Coolia from the Ryukyu Islands, with a description of Coolia kabiraensis sp. nov - Shaun Cunningham; Siratee Riewluang; Aika Yamaguchi; Anne Rolton; Kevin C. Wakeman (Harmful Algae, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Parasitoid releases to manage Queensland fruit fly, Bactrocera tryoni, in southeastern Australia - Lucy K. R. McLay; Joanne C. Dawson; J. Paul Cunningham (BioControl, 2026)
Queensland fruit fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), is Australia’s most economically important horticultural pest. Its range has expanded from its ancestral habitat in rainforests of northeastern Australia into southeastern Australia, and commercial crops. Biocontrol using parasitoid wasps has considerable potential in assisting the area-wide management of B. tryoni in southeastern Australia where they are largely absent. We mass-reared and released two species of parasitoid wasp, Fopius arisanus (Sonan) (Hymenoptera: Braconidae) and Diachasmimorpha kraussii (Fullaway) (Hymenoptera: Braconidae), at six locations in southeastern Australia where they were previously absent. Parasitoid persistence and establishment were monitored over three growing seasons through field collection of B. tryoni infested fruit. Both species parasitised B. tryoni in the field and persisted at the release sites within season. Parasitism rates were up to 63% for D. kraussii and 38% for F. arisanus . D. kraussii were recovered at two of four monitored sites a year after the last releases, indicating the potential of this species to establish in southeastern Australia. In a second study we performed choice and no-choice laboratory experiments to determine if either parasitoid species could target and parasitise the tephritid, Urophora stylata (F.) (Diptera: Tephritidae), which is an established classical biocontrol agent for weed thistles. We found no evidence that either parasitoid can parasitise U. stylata . Our studies indicate that F. arisanus and D. kraussii have potential as biocontrol agents as part of integrated pest management and area-wide management for B. tryoni in southern Australia, with D. kraussii as the more promising candidate.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.

A Synthesis of Factors Related to Trends in Abundance and Demography of Alaska Chinook Salmon ( Oncorhynchus tshawytscha , Salmonidae): Implications for Research, Management, and Policy - Chase C. Lamborn; Jan Ohlberger; Timothy E. Walsworth; Peter A. H. Westley; Curry J. Cunningham; Sam Wynsma; Jordan W. Smith (Fish and Fisheries, 2025)
Across Alaska, there have been synchronous declines in the abundance, mean age, and size of Chinook salmon ( Oncorhynchus tshawytscha , Salmonidae), a species with immense social and ecological importance. The decline of Chinook salmon, and regulations addressing declines, have drastically impacted people who rely on Alaska's fisheries. Despite their importance, the drivers causing Chinook salmon declines are still not well understood. Therefore, to improve our understanding of the likely drivers of these large‐scale synchronous declines, we synthesised the peer‐reviewed Chinook salmon literature published between 2010 and 2024 using a weight‐of‐evidence approach. We identified 94 variables used to explain the trends in abundance and demographics of Chinook salmon. Each variable's association with trends in Chinook salmon was individually assessed and integrated using a standardised method. Results of this synthesis suggest the drivers for large‐scale synchronous declines have occurred in the North Pacific Ocean. Specifically, we found marine predation, size selective harvest, and pink salmon ( Oncorhynchus gorbuscha ) abundance are the factors most strongly associated with reduced size and age. Results also suggest ocean productivity–specifically winter sea surface temperature and the North Pacific Gyre Oscillation–are the most frequently identified predictors of regional Chinook salmon abundance. In addition to addressing freshwater factors like adult heat stress and juvenile predation, we suggest research, policy, and management focus on how to better understand and address the interactions between ocean productivity, marine predation, size selective harvest, and pink salmon abundance to improve the condition of Chinook salmon, and the people and ecosystems benefiting from them.

Long-term trajectories of impacts and recovery of headwater stream temperatures after forest harvest in interior British Columbia - Douglas C. Braun; Dylan S. Cunningham; Herb E. Herunter; Sean M. Naman; Amanda M. Martens (Forest Ecology and Management, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Navigating the risks and rewards of scavenging in multipredator, human‐impacted landscapes - Calum X. Cunningham; Rebecca Windell; Lauren C. Satterfield; Aaron J. Wirsing; Thomas M. Newsome; Taylor R. Ganz; Laura R. Prugh (Ecology, 2025)
Large carnivores can influence smaller scavengers through both positive and negative interactions (e.g., carrion provisioning and intraguild killing) and ultimately shape scavenging efficiency. However, we know little about this trade‐off in anthropogenic landscapes where humans kill carnivores and provide carrion subsidies. In the context of wolf ( Canis lupus ) recolonization of human‐impacted landscapes in Washington, USA, we investigated how sources of ungulate mortality (wolves, cougars [ Puma concolor ], and vehicles) shape scavenging efficiency, community‐wide carcass visitations, and the strategies used by scavengers to navigate risk–reward trade‐offs. Cougar and wolf kills mostly occurred in areas with low‐to‐moderate human influence, whereas roadkill typically occurred in areas with high human impact. Wolves consumed their kills most rapidly (median Cathartes aura ) and black bears ( Ursus americanus ), which are obligate and apex scavengers, respectively, coincided with a seasonal increase in scavenging by most other species. The two mammalian mesocarnivores exhibited divergent strategies: Coyotes ( Canis latrans ) frequently scavenged but usually for short durations and with heightened vigilance at predator kills, whereas bobcats ( Lynx rufus ) visited carcasses less frequently but fed for longer durations and displayed low vigilance while scavenging. These results suggest a hierarchical decision‐making process whereby scavengers first choose whether to forage at a carcass before fine‐tuning foraging duration, using temporal refugia, or increasing vigilance. Predator recovery in human‐dominated landscapes therefore adds complexity to the spatiotemporal landscape of risks and rewards, and outcomes for scavengers will likely depend on their propensity to scavenge and vulnerability to humans and large predators.

Ranavirus in native amphibians from the Pyrenees National Park, France: a case study - Alexandra Peñafiel-Ricaurte; Stephen J. Price; Matthew C. Fisher; Jaime Bosch; Andrew A. Cunningham; Claudio Azat (European Journal of Wildlife Research, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Community-level responses and environmental fate of metformin in freshwater mesocosms - Nicholas C. Blandford; Vince Palace; José Luis Rodríguez-Gil; Lauren Timlick; Madeline Stanley; Richard A. Frank; Sheena Campbell; Martina Rudy; Stephanie Marshall; Abby Wynia; Thomas Clark; Jessie Cunningham; et al. (Science of The Total Environment, 2024)

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Addressing the Boundary and Modifiable Areal Unit Problems Simultaneously when Measuring Landscape Fragmentation Using Patch-Based Metrics: a Case Study of Effective Mesh Size in Nova Scotia, Canada - Caitlin Cunningham; Karen F. Beazley; Peter G. Bush; John C. Brazner (Environmental Modeling & Assessment, 2024)

Effects of metformin on wild fathead minnows (Pimephales promelas) using in-lake mesocosms in a boreal lake ecosystem - Erin Ussery; Mark McMaster; Vince Palace; Joanne Parrott; Nicholas C. Blandford; Richard Frank; Karen Kidd; Oana Birceanu; Joanna Wilson; Mehran Alaee; Jessie Cunningham; Abby Wynia; et al. (Science of The Total Environment, 2024)

Sources of Li isotope bias during SIMS analysis of standard glasses - Adam C. Denny; Mindy M. Zimmer; Heather S. Cunningham; Natalie E. Sievers (Chemical Geology, 2024)

Sweet liking predicts liking and familiarity of some alcoholic beverages, but not alcohol intake: A population study using a split-sample approach - S. Spinelli; C. Cunningham; J. Prescott; E. Monteleone; C. Dinnella; C. Proserpio; T.L. White (Food Research International, 2024)

Economic impacts of marine debris encounters on commercial shrimping - Benedict C. Posadas; Eric L. Sparks; Sarah R. Cunningham; Alyssa E. Rodolfich; Caitlin Wessel; Ryan Bradley (Marine Pollution Bulletin, 2024)

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

Exploring different framings of nature-based solutions with respect to governance, and citizen participation, beneficiaries, and quality of life outcomes - C. Cooper; N. Cunningham; L.J. Bracken (Environmental Science & Policy, 2023)

A co-design method for including stakeholder perspectives in nature-based flood risk management - Jill H. Slinger; Scott C. Cunningham; Baukje L. M. Kothuis (Natural Hazards, 2023)
Intervention methods to establish commitment to (collaborative) action are of potential interest to researchers and policymakers intent upon including stakeholder perspectives in natural risk governance (Scolobig, Nat Hazards 81:27–43, 2016). In this paper, a 6-step co-design method for engaging with local people in collaboratively envisioning nature-based solutions for flood defence is described. The problem structuring base of the participatory method is extended to accommodate the multi-actor situation and the local context of flood risk management. The intervention method is applied in a workshop in the Houston–Galveston Bay area in October 2014. At that time there was strong contestation surrounding the proposed Ike Dike with alternative combinations of nature-based and smaller conventional engineering solutions being proposed. The results indicate that the local participants were able to envision a wide range of future outcomes for the bay and were able to use the insights on nature-based solutions and the social contacts that they acquired at the transdisciplinary workshop to mobilize commitment to joint action. This action focused on collaboration rather than specifying ecological or technical infrastructural requirements and was instrumental in initiating more open discourse on flood defence options for the Houston–Galveston Bay area. The paper concludes that the generic applicability of the co-design method is limited by the requirement to understand and accommodate local circumstances and participants’ insights within the workshop.

Introducing the Ecosystem and Socioeconomic Profile, a Proving Ground for Next Generation Stock Assessments - S. K. Shotwell; K. Blackhart; C. Cunningham; E. Fedewa; D. Hanselman; K. Aydin; M. Doyle; B. Fissel; P. Lynch; O. Ormseth; P. Spencer; S. Zador (Coastal Management, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

Research needs, environmental concerns, and logistical considerations for incorporating livestock grazing into coastal upland habitat management - K. Gill; K.A. Chenier; A. Free; J. Goff; J.L. Pitchford; K. Cressman; M. Posten; E. Brunden; M. Shelton; K. Swanson; S.R. Cunningham; J. Garland; et al. (Journal of Environmental Management, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Controls on the stratigraphic distribution of organic carbon in ancient deep-marine levees - Celeste M. Cunningham; Simona F. Ruso; R. William C. Arnott (Marine and Petroleum Geology, 2023)

The transport and fate of microplastic fibres in the Antarctic: The role of multiple global processes - Eoghan M. Cunningham; Nuria Rico Seijo; Katye E. Altieri; Riesna R. Audh; Jessica M. Burger; Thomas G. Bornman; Sarah Fawcett; Claire M. B. Gwinnett; Amy O. Osborne; Lucy C. Woodall (Frontiers in Marine Science, 2022)
Understanding the transport and accumulation of microplastics is useful to determine the relative risk they pose to global biodiversity. The exact contribution of microplastic sources is hard to elucidate; therefore, investigating the Antarctic Weddell Sea, an area known for its remoteness and little human presence (i.e. limited pollution sources), will help us to better understand microplastic transportation. Here, we investigate the presence of microplastics in a range of Antarctic sample media including air, seawater, and sediment. We hypothesised that multiple transportation processes including atmospheric and oceanic vectors determine the presence of microplastics in the Antarctic. Using techniques including Polarised Light Microscopy and Raman Spectrometry, we identified mostly fibres and categorised them based on their optical and chemical properties. A total of 47 individual microplastic categories (45 of which were fibres) were identified in the air, seawater, and sediment samples. The majority of categories did not overlap multiple media (42/47); however, four fibre categories were present in both air and water samples, and another fibre category was found in all three media (category 27). We suggest that the large variety of fibres identified and the overlap of fibre categories among media indicates that the pollution may result from multiple diffuse sources and transportation pathways. Additionally, our Air Mass Back Trajectory analyses demonstrates that microplastic fibres are being transported by air masses or wind, and strongly suggests that they are transported to the Antarctic from southern South America. We also propose that fibres may be transported into the Antarctic in subsurface waters, and as pollution was identified in our sediment and additional sea ice samples, we suggest that the coastal and Antarctic deep sea may be a sink for microplastic fibres. The results shown here from a remote, near-pristine system, further highlight the need for a global response to the plastic pollution crisis.

Gene expression underlying parenting and being parented shows limited plasticity in response to different ambient temperatures - Jeanette B. Moss; Christopher B. Cunningham; Elizabeth C. McKinney; Allen J. Moore (Molecular Ecology, 2022)
Flexible interactions between parents and offspring are essential for buffering families against variable, unpredictable, and challenging environmental conditions. In the subsocial carrion beetle, Nicrophorus orbicollis , mid‐summer temperatures impose steep fitness costs on parents and offspring but do not elicit behavioural plasticity in parents. Here, we ask if plasticity of gene expression underpins this behavioural stability or facilitates independent compensation by larvae. To test this, we characterized gene expression of parents and offspring before and during active parenting under benign (20°C) and stressful (24°C) temperatures to identify genes of parents and offspring associated with thermal response, parenting/being parented, and gene expression plasticity associated with behavioural stability of parental care. The main effects of thermal and social condition each shaped patterns of gene expression in females, males, and larvae. In addition, we implicated 79 genes in females as “buffering” parental behaviour across environments. The majority of these underwent significant changes in expression in actively parenting mothers at the benign temperature, but not at the stressful temperature. Our results suggest that neither genetic programmes for parenting nor their effects on offspring gene expression are fundamentally different under stressful conditions, and that behavioural stability is associated primarily with the maintenance of existing genetic programmes rather than replacement or supplementation. Thus, while selection for compensatory gene expression could expand the range of thermal conditions parents will tolerate, without expanding the toolkit of genes involved selection is unlikely to lead to adaptive changes of function.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Examining the Role of Marine Mammals and Seabirds in Southeast Alaska’s Marine Ecosystem Dynamics - Melissa Rhodes-Reese; David Clay; Curry Cunningham; Janet Moriles-Miller; Cheryl Reese; Joe Roman; Joseph D. Warren; Heidi C. Pearson (Frontiers in Marine Science, 2021)
Primary producers are the foundation of marine food webs and require reliable nutrient sources to maintain their important role with ecosystems. While marine mammals and seabirds can play critical roles in marine nutrient cycling, their contributions are often overlooked. Southeast Alaska’s marine environment supports abundant marine mammal and seabird populations in addition to valuable fisheries. Nonetheless, there is still relatively little known about nutrient sources and fluxes in this region which is a critical component of fisheries management. The goal of our study was to advance knowledge of the role of mammals and seabirds in marine nutrient cycling and to understand how changing marine mammal and seabird populations may alter ecosystem dynamics. We utilized qualitative network models (QNMs) to examine how a simulated Southeast Alaska ecosystem would respond to an increase in marine mammals, seabirds, and nutrients. Researchers are increasingly utilizing QNMs as a first step in the development of ecosystem-based fisheries management plans as their adaptable nature is well suited to address rapidly changing climatic conditions. Our results indicate that marine mammals and seabirds make important contributions to marine nutrient concentrations in the region and that these valuable ecosystem services should not be overlooked.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A pilot study of a culturally-appropriate, educational intervention to increase participation in cancer clinical trials among African Americans and Latinos - Jennifer Cunningham-Erves; Tilicia L. Mayo-Gamble; Pamela C. Hull; Tao Lu; Claudia Barajas; Caree R. McAfee; Maureen Sanderson; Juan R. Canedo; Katina Beard; Consuelo H. Wilkins (Cancer Causes & Control, 2021)

A novel knockout mouse for the small EDRK-rich factor 2 (Serf2) showing developmental and other deficits - Karen Cleverley; Weaverly Colleen Lee; Paige Mumford; Toby Collins; Matthew Rickman; Thomas J. Cunningham; James Cleak; Joffrey Mianne; Zsombor Szoke-Kovacs; Michelle Stewart; Lydia Teboul; Cheryl Maduro; et al. (Mammalian Genome, 2021)
The small EDRK-rich factor 2 (SERF2) is a highly conserved protein that modifies amyloid fibre assembly in vitro and promotes protein misfolding. However, the role of SERF2 in regulating age-related proteotoxicity remains largely unexplored due to a lack of in vivo models. Here, we report the generation of Serf2 knockout mice using an ES cell targeting approach, with Serf2 knockout alleles being bred onto different defined genetic backgrounds. We highlight phenotyping data from heterozygous Serf2 +/− mice, including unexpected male-specific phenotypes in startle response and pre-pulse inhibition. We report embryonic lethality in Serf2 −/− null animals when bred onto a C57BL/6 N background. However, homozygous null animals were viable on a mixed genetic background and, remarkably, developed without obvious abnormalities. The Serf2 knockout mice provide a powerful tool to further investigate the role of SERF2 protein in previously unexplored pathophysiological pathways in the context of a whole organism.

Utility of DNA barcoding in native Oreochromis species - Tonna O. Mojekwu; Michael J. Cunningham; Roger I. Bills; Petrus C. Pretorius; Thierry B. Hoareau (Journal of Fish Biology, 2021)
The importance of Oreochromis in worldwide aquaculture and regional fisheries motivates the study of their genetic diversity in their native range. In this article, all mitochondrial cytochrome c oxidase subunit I gene (COI) sequences of Oreochromis species are retrieved from Barcode of Life Data system to quantify the available DNA barcoding information from wild individuals collected within the native ranges of the respective species. It is found that 70% of the known species in the genus still lack a COI barcode, and only 15% of the available sequences are from within the respective native ranges. Many of the available sequences have been produced from specimens acquired from aquaculture and introduced, naturalized populations, making the assessment of variation within the original native range challenging. Analyses of the wild‐collected fraction of available sequences indicated the presence of cryptic lineages within Nile tilapia Oreochromis niloticus and O. schwebischi , the occurrence of potential introgressive hybridization between O. niloticus and blue tilapia O. aureus , and potential ancestral polymorphism between Karonga tilapia O. karongae and black tilapia O. placidus . This article also reports a case of misidentification of O. mweruensis as longfin tilapia O. macrochir . These results stress the importance of improving the knowledge of genetic variation within the native ranges of Oreochromis species for better‐informed conservation of these natural resources.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Marker associations for fusiform rust resistance in a clonal population of loblolly pine (Pinus taeda, L.) - W. Patrick Cumbie; Dudley A. Huber; Victor C. Steel; William Rottmann; Christina Cannistra; Les Pearson; Michael Cunningham (Tree Genetics & Genomes, 2020)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Correction to: Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Vitellogenesis in spiders: first analysis of protein changes in different reproductive stages of Polybetes pythagoricus - S. Romero; A. Laino; F. Arrighetti; C. F. García; M. Cunningham (Journal of Comparative Physiology B, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Clinicians’ use of breast cancer risk assessment tools according to their perceived importance of breast cancer risk factors: an international survey - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Marjanka K. Schmidt; Sylvie Dolbeault; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Journal of Community Genetics, 2019)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Corrections to: Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean‑Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

Use of the BOADICEA Web Application in clinical practice: appraisals by clinicians from various countries - Anne Brédart; Jean-Luc Kop; Antonis C. Antoniou; Alex P. Cunningham; Antoine De Pauw; Marc Tischkowitz; Hans Ehrencrona; Sylvie Dolbeault; Léonore Robieux; Kerstin Rhiem; Douglas F. Easton; Peter Devilee; et al. (Familial Cancer, 2018)

Morphological, ecological and behavioural differentiation of sympatric profundal and pelagic Arctic charr (Salvelinus alpinus) in Loch Dughaill Scotland - O. E. Hooker; J. Barry; T. E. Van Leeuwen; A. Lyle; J. Newton; P. Cunningham; C. E. Adams (Hydrobiologia, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Warfare in stingless bees - C. Grüter; L. G. von Zuben; F. H. I. D. Segers; J. P. Cunningham (Insectes Sociaux, 2016)

Effects of fendiline on cocaine-seeking behavior in the rat - Jonathan J. Cunningham; Erin Orr; Barbara C. Lothian; Jennifer Morgen; Karen Brebner (Psychopharmacology, 2015)

Public concerns regarding the storage and secondary uses of residual newborn bloodspots: an analysis of print media, legal cases, and public engagement activities - Shannon Cunningham; Kieran C. O’Doherty; Karine Sénécal; David Secko; Denise Avard (Journal of Community Genetics, 2015)

Reforestation with native mixed‐species plantings in a temperate continental climate effectively sequesters and stabilizes carbon within decades - Shaun C. Cunningham; Timothy R. Cavagnaro; Ralph Mac Nally; Keryn I. Paul; Patrick J. Baker; Jason Beringer; James R. Thomson; Ross M. Thompson (Global Change Biology, 2015)
Reforestation has large potential for mitigating climate change through carbon sequestration. Native mixed‐species plantings have a higher potential to reverse biodiversity loss than do plantations of production species, but there are few data on their capacity to store carbon. A chronosequence (5–45 years) of 36 native mixed‐species plantings, paired with adjacent pastures, was measured to investigate changes to stocks among C pools following reforestation of agricultural land in the medium rainfall zone (400–800 mm yr −1 ) of temperate Australia. These mixed‐species plantings accumulated 3.09 ± 0.85 t C ha −1 yr −1 in aboveground biomass and 0.18 ± 0.05 t C ha −1 yr −1 in plant litter, reaching amounts comparable to those measured in remnant woodlands by 20 years and 36 years after reforestation respectively. Soil C was slower to increase, with increases seen only after 45 years, at which time stocks had not reached the amounts found in remnant woodlands. The amount of trees (tree density and basal area) was positively associated with the accumulation of carbon in aboveground biomass and litter. In contrast, changes to soil C were most strongly related to the productivity of the location (a forest productivity index and soil N content in the adjacent pasture). At 30 years, native mixed‐species plantings had increased the stability of soil C stocks, with higher amounts of recalcitrant C and higher C : N ratios than their adjacent pastures. Reforestation with native mixed‐species plantings did not significantly change the availability of macronutrients (N, K, Ca, Mg, P, and S) or micronutrients (Fe, B, Mn, Zn, and Cu), content of plant toxins (Al, Si), acidity, or salinity (Na, electrical conductivity) in the soil. In this medium rainfall area, native mixed‐species plantings provided comparable rates of C sequestration to local production species, with the probable additional benefit of providing better quality habitat for native biota. These results demonstrate that reforestation using native mixed‐species plantings is an effective alternative for carbon sequestration to standard monocultures of production species in medium rainfall areas of temperate continental climates, where they can effectively store C, convert C into stable pools and provide greater benefits for biodiversity.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Physicochemical and Formulation Developability Assessment for Therapeutic Peptide Delivery—A Primer - Annette Bak; Dennis Leung; Stephanie E. Barrett; Seth Forster; Ellen C. Minnihan; Andrew W. Leithead; James Cunningham; Nathalie Toussaint; Louis S. Crocker (The AAPS Journal, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Low Back Pain Among Irish Farmers - A. Osborne; C. Blake; D. Meredith; J. McNamara; J. Phelan; C. Cunningham (Journal of Agromedicine, 2014)

Psittacine beak and feather disease in a free-living ring-necked parakeet (Psittacula krameri) in Great Britain - Ricardo C. C. Sa; Andrew A. Cunningham; Mark P. Dagleish; Nick Wheelhouse; Ann Pocknell; Nicole Borel; Hannah L. Peck; Becki Lawson (European Journal of Wildlife Research, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Climate‐change‐driven deterioration of the condition of floodplain forest and the future for the avifauna - Ralph Mac Nally; Hania Lada; Shaun C. Cunningham; James R. Thomson; Erica Fleishman (Global Ecology and Biogeography, 2014)
Aim We used models of remotely sensed estimates of forest‐stand condition (degree of die‐back) with models of avian responses to stand condition to determine how the avifauna responded to a 13‐year drought, and how the avifauna might respond to a predicted much warmer and drier climate in the next 60 years. Location Floodplain forests of the southern M urray– D arling B asin, A ustralia. Methods We selected 45 2‐ha locations that spanned the full range of stand condition and conducted bird surveys and rapid assessments of breeding, which involved repeated measurements over the breeding season. These values were modelled as functions of stand condition and several other on‐site predictors. We made hindcast estimates of the proportions of forest in different stand‐condition classes. We developed a trajectory of change in these proportions under the regionally downscaled estimates of climate change under the A1F1 IPCC emission scenario, which were linked with patterns of change in drier, hotter extant forests. The hindcast and projected values were coupled with the results of the statistical models for the avifauna to provide future projections for the avifauna. Results Three avifaunal variables (measures of abundance, effective species richness and total breeding score summed for all species) were strongly related to stand condition. Hindcast estimates based on the assumption of original good condition suggested that the response variables had declined by > 25% since 1750. Projected declines in the response variables from 2009 to 2070 were > 29%, while differences between 1750 and 2070 were > 58%. Conclusions Stand condition strongly influences birds, so that reliable estimates of avifaunal change can be made by using remotely sensed estimates of stand condition. Given probable changes in forest condition under climate change, we project that the prospects for these avifauna are dire under the A1F1 or more extreme emission scenarios.

The interaction between a drying climate and land use affects forest structure and above‐ground carbon storage - Joanne M. Bennett; Shaun C. Cunningham; Christine A. Connelly; Rohan H. Clarke; James R. Thomson; Ralph Mac Nally (Global Ecology and Biogeography, 2013)
Aim Climate change has been linked to negative effects on vegetation, including drought‐induced dieback. Large‐scale dieback not only leads to considerable carbon emissions but often leads to loss of ecological resources. We investigated whether, and how, the structure, composition and carbon content changed over a period of extended drought (the ‘ B ig D ry’) in a much‐modified forest ecosystem. We explored whether landscape configuration, management practice or soil type influenced vegetation change. Location The B ox‐ I ronbark forests of south‐eastern A ustralia. Methods In 2010, we remeasured 120 forest transects that had first been measured in 1997 by using identical field methods. Vegetation structure and composition were quantified. We used allometric growth models to estimate the expected increase in above‐ground carbon ( AGC ) storage between 1997 and 2010; these estimates were compared with observed values. Results Forest structure was systematically different between the two periods. Canopy cover, shrub cover and litter decreased between the 1997 and 2010 surveys, whereas total basal area of dead trees, dead trees in all size classes and saplings increased between the two surveys. Climate, fragment size and their interaction were the major predictors of change in most of the measured vegetation characteristics. By comparing measured AGC in 2010 and estimates from growth models, we estimated that 5.6 ± 2.1 SE t C ha −1 may have been foregone over the B ig D ry. Main conclusions Our findings add to the evidence linking climate change to negative effects on vegetation, including mortality, canopy dieback and reduced carbon sequestration. These effects may be amplified in fragmented vegetation because of greater water and heat stress. If the carbon sequestration deficit of c. 5.6 t C ha −1 were to apply across the extant Box‐Ironbark forests of V ictoria ( c . 255,400 ha), then 1.43 M t of carbon sequestration may not have occurred during the B ig D ry.

Engineered applications of ureolytic biomineralization: a review - Adrienne J. Phillips; Robin Gerlach; Ellen Lauchnor; Andrew C. Mitchell; Alfred B. Cunningham; Lee Spangler (Biofouling, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

The influences of climatic variation and vegetation on stream biota: lessons from the B ig D ry in southeastern A ustralia - James R. Thomson; Nick R. Bond; Shaun C. Cunningham; Leon Metzeling; Paul Reich; Ross M. Thompson; Ralph Mac Nally (Global Change Biology, 2012)
Aquatic biodiversity faces increasing threats from climate change, escalating exploitation of water and land use intensification. Loss of vegetation in catchments (= watersheds) has been identified as a substantial problem for many river basins, and there is an urgent need to better understand how climate change may interact with changes in catchment vegetation to influence the ecological condition of freshwater ecosystems. We used 20 years of biological monitoring data from V ictoria, southeastern A ustralia, to explore the influences of catchment vegetation and climate on stream macroinvertebrate assemblages. Southeastern A ustralia experienced a severe drought from 1997 to 2009, with reductions of stream flows >50% in some areas. The prolonged drying substantially altered macroinvertebrate assemblages, with reduced prevalence of many flow‐dependent taxa and increased prevalence of taxa that are tolerant of low‐flow conditions and poor water quality. Stream condition, as assessed by several commonly used macroinvertebrate indices, was consistently better in reaches with extensive native tree cover in upstream catchments. Prolonged drought apparently caused similar absolute declines in macroinvertebrate condition indices regardless of vegetation cover, but streams with intact catchment and riparian vegetation started in better condition and remained so throughout the drought. The largest positive effects of catchment tree cover on both water quality and macroinvertebrate assemblages occurred above a threshold of ca. 60% areal tree cover in upstream catchments and in higher rainfall areas. Riparian tree cover also had positive effects on macroinvertebrate assemblages, especially in warmer catchments. Our results suggest that the benefits of extensive tree cover via improved water quality and in‐channel habitat persist during drought and show the potential for vegetation management to reduce negative impacts of climatic extremes for aquatic ecosystems.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Endotoxin-induced HIF-1α stabilisation in equine endothelial cells: synergistic action with hypoxia - A. C. Brooks; N. Menzies-Gow; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2010)

Impact of hydrographic data assimilation on the modelled Atlantic meridional overturning circulation - G. C. Smith; K. Haines; T. Kanzow; S. Cunningham (Ocean Science, 2010)
Here we make an initial step toward the development of an ocean assimilation system that can constrain the modelled Atlantic Meridional Overturning Circulation (AMOC) to support climate predictions. A detailed comparison is presented of 1° and 1/4° resolution global model simulations with and without sequential data assimilation, to the observations and transport estimates from the RAPID mooring array across 26.5° N in the Atlantic. Comparisons of modelled water properties with the observations from the merged RAPID boundary arrays demonstrate the ability of in situ data assimilation to accurately constrain the east-west density gradient between these mooring arrays. However, the presence of an unconstrained "western boundary wedge" between Abaco Island and the RAPID mooring site WB2 (16 km offshore) leads to the intensification of an erroneous southwards flow in this region when in situ data are assimilated. The result is an overly intense southward upper mid-ocean transport (0–1100 m) as compared to the estimates derived from the RAPID array. Correction of upper layer zonal density gradients is found to compensate mostly for a weak subtropical gyre circulation in the free model run (i.e. with no assimilation). Despite the important changes to the density structure and transports in the upper layer imposed by the assimilation, very little change is found in the amplitude and sub-seasonal variability of the AMOC. This shows that assimilation of upper layer density information projects mainly on the gyre circulation with little effect on the AMOC at 26° N due to the absence of corrections to density gradients below 2000 m (the maximum depth of Argo). The sensitivity to initial conditions was explored through two additional experiments using a climatological initial condition. These experiments showed that the weak bias in gyre intensity in the control simulation (without data assimilation) develops over a period of about 6 months, but does so independently from the overturning, with no change to the AMOC. However, differences in the properties and volume transport of North Atlantic Deep Water (NADW) persisted throughout the 3 year simulations resulting in a difference of 3 Sv in AMOC intensity. The persistence of these dense water anomalies and their influence on the AMOC is promising for the development of decadal forecasting capabilities. The results suggest that the deeper waters must be accurately reproduced in order to constrain the AMOC.

Factors driving pathogenicity vs. prevalence of amphibian panzootic chytridiomycosis in Iberia - Susan F. Walker; Jaime Bosch; Virgilio Gomez; Trenton W. J. Garner; Andrew A. Cunningham; Dirk S. Schmeller; Miguel Ninyerola; Daniel A. Henk; Cedric Ginestet; Christian‐Philippe Arthur; Matthew C. Fisher (Ecology Letters, 2010)
Ecology Letters (2010) 13: 372–382 Abstract Amphibian chytridiomycosis is a disease caused by the fungus Batrachochytrium dendrobatidis ( Bd ). Whether Bd is a new emerging pathogen (the novel pathogen hypothesis; NPH) or whether environmental changes are exacerbating the host‐pathogen dynamic (the endemic pathogen hypothesis; EPH) is debated. To disentangle these hypotheses we map the distribution of Bd and chytridiomycosis across the Iberian Peninsula centred on the first European outbreak site. We find that the infection‐free state is the norm across both sample sites and individuals. To analyse this dataset, we use Bayesian zero‐inflated binomial models to test whether environmental variables can account for heterogeneity in both the presence and prevalence of Bd, and heterogeneity in the occurrence of the disease, chytridiomycosis. We also search for signatures of Bd ‐spread within Iberia using genotyping. We show (1) no evidence for any relationship between the presence of Bd and environmental variables, (2) a weak relationship between environmental variables and the conditional prevalence of infection, (3) stage‐dependent heterogeneity in the infection risk, (4) a strong association between altitude and chytridiomycosis, (5) multiple Iberian genotypes and (6) recent introduction and spread of a single genotype of Bd in the Pyrenees. We conclude that the NPH is consistent with the emergence of Bd in Iberia. However, epizootic forcing of infection is tied to location and shaped by both biotic and abiotic variables. Therefore, the population‐level consequences of disease introduction are explained by EPH‐like processes. This study demonstrates the power of combining surveillance and molecular data to ascertain the drivers of new emerging infections diseases.

Mortality of developing floodplain forests subjected to a drying climate and water extraction - GILLIS J. HORNER; PATRICK J. BAKER; RALPH MAC NALLY; SHAUN C. CUNNINGHAM; JAMES R. THOMSON; FIONA HAMILTON (Global Change Biology, 2009)
River regulation and water extraction have altered the hydrology of rivers resulting in substantial changes to forest structure and the dieback of floodplain forests globally. Forest mortality, due to water extraction, is likely to be exacerbated by climate change‐induced droughts. In 1965, a plantation trial was established within a natural floodplain forest to examine the effect of planting density on timber production. We used data from this trial to investigate the effect of initial stand density on the structure and dynamics of Eucalyptus camaldulensis (Dehnh.) forests. Highest density stands (8000 trees ha −1 ) were dominated by many slender trees, mostly

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

Patterns in the distribution of myctophid fish in the northern Scotia Sea ecosystem - Martin A. Collins; Jose C. Xavier; Nadine M. Johnston; Anthony W. North; Peter Enderlein; Geraint A. Tarling; Claire M. Waluda; Elizabeth J. Hawker; Nathan J. Cunningham (Polar Biology, 2008)

How to Use Genetic Data to Distinguish Between Natural and Human-Mediated Introduction of Littorina littorea to North America - C. W. Cunningham (Biological Invasions, 2008)

The differential diagnosis of vertical strabismus from prism cover test data using an artificially intelligent expert system - Anthony C. Fisher; Arvind Chandna; Ian P. Cunningham (Medical & Biological Engineering & Computing, 2007)

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

Endotoxin-induced activation of equine platelets: evidence for direct activation of p38 MAPK pathways and vasoactive mediator production - A. C. Brooks; N. J. Menzies-Gow; C. Wheeler-Jones; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2007)

Genetic consequences of habitat fragmentation and loss: the case of the Florida black bear (Ursus americanus floridanus) - Jeremy D. Dixon; Madan K. Oli; Michael C. Wooten; Thomas H. Eason; J. Walter McCown; Mark W. Cunningham (Conservation Genetics, 2007)

Nearshore fish ( Pholis gunnellus ) persists across the North Atlantic through multiple glacial episodes - M. J. HICKERSON; C. W. CUNNINGHAM (Molecular Ecology, 2006)
The intertidal biota of the North Atlantic is characterized by two disjunct communities (North American and European) exposed to different climatic regimes during the Pleistocene and in the Holocene. We collect multilocus DNA sequence data from the nearshore fish Pholis gunnellus to help uncover processes determining biogeographical persistence during periodic coastal glaciations. Coalescent‐based estimates from the multilocus DNA sequence data suggest that P. gunnellus persisted on both sides of the North Atlantic throughout the last two glacial maxima (> 202 000 years) with little trans‐Atlantic gene flow since divergence, very little structure among populations within Europe (Φ ST ST = 0.0–0.21). Although the ecological flexibility and high local migration of P. gunnellus could have enhanced this species’ survival across the Atlantic, logistic regression did not find a significant determinant of trans‐Atlantic persistence when considering 12 other North Atlantic phylogeographical studies from the literature.

Development of an Advanced Hyperspectral Imaging (HSI) System with Applications for Cancer Detection - Matthew E. Martin; Musundi B. Wabuyele; Kui Chen; Paul Kasili; Masoud Panjehpour; Mary Phan; Bergein Overholt; Glenn Cunningham; Dale Wilson; Robert C. DeNovo; Tuan Vo-Dinh (Annals of Biomedical Engineering, 2006)

Feline Immunodeficiency Virus and Puma Lentivirus in Florida panthers (Puma concolor coryi): Epidemiology and Diagnostic Issues - D. L. Miller; S. K. Taylor; D. S. Rotstein; M. B. Pough; M. C. Barr; C. A. Baldwin; M. Cunningham; M. Roelke; D. Ingram (Veterinary Research Communications, 2006)

Equine CCL11 induces eosinophil cytoskeletal reorganization and activation - M. C. Weston; M. E. Collins; F. M. Cunningham (Inflammation Research, 2006)

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Role of the serotonin 5-HT2A receptor in the hyperlocomotive and hyperthermic effects of (+)-3,4-methylenedioxymethamphetamine - David V. Herin; Shijing Liu; Thomas Ullrich; Kenner C. Rice; Kathryn A. Cunningham (Psychopharmacology, 2005)

The role of protein kinase C in regulating equine eosinophil adherence and superoxide production - M. F. Sepulveda; E. C. Greenaway; M. Avella; N. T. Goode; F. M. Cunningham (Inflammation Research, 2005)

Photosynthetic responses to vapour pressure deficit in temperate and tropical evergreen rainforest trees of Australia - S. C. Cunningham (Oecologia, 2005)

INVITED REVIEW: Local adaptation and species segregation in two mussel ( Mytilus edulis × Mytilus trossulus ) hybrid zones - C. RIGINOS; C. W. CUNNINGHAM (Molecular Ecology, 2005)
Few marine hybrid zones have been studied extensively, the major exception being the hybrid zone between the mussels Mytilus edulis and Mytilus galloprovincialis in southwestern Europe. Here, we focus on two less studied hybrid zones that also involve Mytilus spp.; Mytilus edulis and Mytilus trossulus are sympatric and hybridize on both western and eastern coasts of the Atlantic Ocean. We review the dynamics of hybridization in these two hybrid zones and evaluate the role of local adaptation for maintaining species boundaries. In Scandinavia, hybridization and gene introgression is so extensive that no individuals with pure M. trossulus genotypes have been found. However, M. trossulus alleles are maintained at high frequencies in the extremely low salinity Baltic Sea for some allozyme genes. A synthesis of reciprocal transplantation experiments between different salinity regimes shows that unlinked Gpi and Pgm alleles change frequency following transplantation, such that post‐transplantation allelic composition resembles native populations found in the same salinity. These experiments provide strong evidence for salinity adaptation at Gpi and Pgm ( or genes linked to them). In the Canadian Maritimes, pure M. edulis and M. trossulus individuals are abundant, and limited data suggest that M. edulis predominates in low salinity and sheltered conditions, whereas M. trossulus are more abundant on the wave‐exposed open coasts. We suggest that these conflicting patterns of species segregation are, in part, caused by local adaptation of Scandinavian M. trossulus to the extremely low salinity Baltic Sea environment.

Mitochondrial evolution and phylogeography in the hydrozoan Obelia geniculata (Cnidaria) - A. F. Govindarajan; K. M. Halanych; C. W. Cunningham (Marine Biology, 2005)

Expanding GSK?s Solvent Selection Guide?application of life cycle assessment to enhance solvent selections - Concepcin Jimnez-Gonzlez; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (Clean Technologies and Environmental Policy, 2004)

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

Cradle-to-gate life cycle inventory and assessment of pharmaceutical compounds - Conceptión Jiménez-González; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2004)

Causes and Effects of Temporospatial Declines of Gyps Vultures in Asia - D. J. Pain; A. A. Cunningham; P. F. Donald; J. W. Duckworth; D. C. Houston; T. Katzner; J. Parry‐Jones; C. Poole; V. Prakash; P. Round; R. Timmins (Conservation Biology, 2003)

Compensation for herbivory by Cucumis sativus through increased photosynthetic capacity and efficiency - Vivien P. Thomson; Saul A. Cunningham; Marilyn C. Ball; Adrienne B. Nicotra (Oecologia, 2003)

The sodium channel blocker RS100642 reverses down-regulation of the sodium channel α-subunit Nav 1.1 expression caused by transient ischemic brain injury in rats - C. Yao; A. J. Williams; X. -C. M. Lu; R. A. Price; B. S. Cunningham; R. Berti; F. C. Tortella; J. R. Dave (Neurotoxicity Research, 2003)

Mechanisms of competition: thermal inhibition of tree seedling growth by grass - Marilyn C. Ball; J. Egerton; Jason L. Lutze; Vincent P. Gutschick; Ross B. Cunningham (Oecologia, 2002)

Investigation of genetic diversity in fragmented geometric tortoise (Psammobates geometricus) populations - J. Cunningham; E.H.W. Baard; E.H. Harley; C. O'Ryan (Conservation Genetics, 2002)

Morphological and genetic evidence for vicariance and refugium in Atlantic and Gulf of Mexico populations of the hermit crab Pagurus longicarpus - Young A.; Torres C.; Mack J.; Cunningham C. (Marine Biology, 2002)

Factors affecting the presence of the cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ) in southern Australia: integrating climatic, terrain and disturbance predictors of distribution patterns - D. B. Lindenmayer; B. G. Mackey; R. B. Cunningham; C. F. Donnelly; I. C. Mullen; M. A. McCarthy; A. M. Gill (Journal of Biogeography, 2000)
Aim This study identified the factors influencing the presence, stocking rate and basal area of the southern Australian cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ). Location This investigation was conducted in the montane ash forests of the Central Highlands of Victoria, south‐eastern Australia. Methods The occurrence of N. cunninghamii was measured as part of field surveys of 474 sites (2844 plots) distributed widely throughout mountain ash ( Eucalyptus regnans ), alpine ash ( E. delegatensis ) and shining gum ( E. nitens ) forests. Statistical analysis was employed to examine relationships between the occurrence of N. cunninghamii and measured site attributes and interpolated and derived environmental variables. Results The presence of N. cunninghamii was significantly related to five variables: the age of the overstorey eucalypt stand, dominant species of overstorey eucalypt tree, topographic position in the landscape, slope and the estimated quantity of precipitation in the warmest quarter of the year. N. cunninghamii was more likely to occur in old growth eucalypt stands, in gullies and locations with high values for rainfall in the warmest quarter. In addition, there was an interaction between slope and dominant eucalypt tree species—in forests dominated by E. regnans , N. cunninghamii was more likely to occur on steep slopes whereas in E. nitens and E. delegatensis ‐dominated stands, N. cunninghamii was more likely to occur on flatter terrain. Statistical modelling also showed a significant positive effect of slope on both the stocking rate and basal area of the species. The stocking rate of N. cunninghamii also was significantly higher in old growth eucalypt stands. Main conclusions The study demonstrated that the patterns of distribution of N. cunninghamii may be more complex than recognized previously and it illustrated the importance of multiple factors including climatic conditions, disturbance processes (as reflected through the age of the dominant overstorey eucalypt stands) and topography. Our work also shows there can be complex interactions between age cohorts of different tree species in the same stand—in this case, the dominant overstorey eucalypts and the understorey which includes N. cunninghamii stems.

Molecular cloning of the gene for interleukin-1? from Xenopus laevis and analysis of expression in vivo and in vitro - J. Zou; S. Bird; C. Cunningham; C. J. Secombes; J. Horton; R. Minter (Immunogenetics, 2000)

Influence of nitrogen, photoperiod, cutting type, and clone on root and shoot development of rooted stem cuttings of sweetgum - Heidi Rieckermann; Barry Goldfarb; Michael W. Cunningham; Robert C. Kellison (New Forests, 1999)

Diminished energy metabolism and enhanced apoptosis in livers of B6C3F1 mice treated with the antihepatocarcinogen rotenone - C. Wang; J. Youssef; B. Saran; P.G. Rothberg; M.L. Cunningham; A. Molteni; M. Badr (Molecular and Cellular Biochemistry, 1999)

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

The captive rearing of threatened Orthoptera: a comparison of the conservation potential and practical considerations of two species' breeding programmes at the Zoological Society of London - P. Pearce-Kelly; R. Jones; D. Clarke; C. Walker; P. Atkin; A.A. Cunningham (Journal of Insect Conservation, 1998)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

Comparative phylogeography and the history of endemic vertebrates in the Wet Tropics rainforests of Australia - C. J. SCHNEIDER; M. CUNNINGHAM; C. MORITZ (Molecular Ecology, 1998)
We examine the effects of historical climate change on vertebrate differentiation in tropical rainforest by comparing phylogeographic patterns in six species of widespread rainforest‐restricted herpetofauna from throughout the Wet Tropics of Australia. Qualitative and quantitative comparisons of phylogeographic structure reveal strikingly similar patterns of pre‐Pleistocene vicariant population differentiation on either side of a previously identified biogeographic break (variously referred to as the Black Mountain Barrier or Corridor; BMC). While divergence across the BMC antedates the Pleistocene, the impact of Quaternary climate change is apparent in populations on either side of the BMC. Consistent with palaeoclimatological reconstructions for the region, the distribution and degree of mtDNA diversity suggests that populations were fragmented and reduced to multiple refugia during Pleistocene glacial periods, with expansion following Holocene rainforest recovery. This pattern is repeated on both sides of the BMC, but substantial differences in the amount and distribution of mtDNA diversity within species indicate the importance of species‐specific ecological characteristics. The historical processes of extinction and (re)colonization revealed by the comparative phylogeographic analysis of mtDNA sequences substantiate earlier suggestions that current regional patterns of species distribution and diversity in the Wet Tropics are largely determined by local extinctions and subsequent recolonization driven by Quaternary climate changes.

Sucrose requirements and lipid utilization during germination of interior spruce (Picea glauca engelmannii complex) somatic embryos - D. J. Carrier; J. E. Cunningham; D. C. Taylor; D. I. Dunstan (Plant Cell Reports, 1997)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Campbell 14: A verticillium resistant round white potato variety - A. F. Reeves; C. E. Cunningham; R. L. Nickeson; R. V. Akeley; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1985)

Sunrise: An early maturing, golden nematode resistant, round, white potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1985)

Yankee Supreme: A new bruise-resistant potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; R. L. Nickeson; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1984)

Chronic effects of ingested asbestos in rats - H. M. Cunningham; C. A. Moodie; G. A. Lawrence; R. D. Pontefract (Archives of Environmental Contamination and Toxicology, 1977)

Internal quality of Russet Burbank potatoes following chilling - Helen H. Cunningham; Mary V. Zaehringer; Goldie Brausen; W. C. Sparks (American Journal of Potato Research, 1976)

Leaching of solutes and sloughing of potato tuber tissue - W. C. Davis; D. J. Le Tourneau; Mary V. Zaehringer; Helen H. Cunningham (American Journal of Potato Research, 1973)

John C. Campbell honored - C. E. Cunningham (American Journal of Potato Research, 1972)

Storage temperature for maintenance of internal quality in Idaho Russet Burbank potatoes - Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks (American Journal of Potato Research, 1971)

Genetics of the potato, Solanum tuberosum. H. W. Howard - C. E. Cunningham (American Journal of Potato Research, 1971)

Wauseon: A new potato variety resistant to golden nematode with good processing quality - C. E. Cunningham; R. V. Akeley; L. C. Peterson; T. E. Snyder (American Journal of Potato Research, 1968)

Lenape: A new potato variety high in solids and chipping quality - R. V. Akeley; W. R. Mills; C. E. Cunningham; James Watts (American Journal of Potato Research, 1968)

Replication and cytopathogenicity of avian infectious bronchitis virus in chicken embryo kidney cells - T. G. Akers; C. H. Cunningham (Archives of Virology, 1968)

Inheritance of resistance to Verticillium wilt in Wisconsin - D. E. Hunter; H. M. Darling; F. J. Stevenson; C. E. Cunningham (American Journal of Potato Research, 1968)

Sugar content and color of Russet Burbank potatoes as related to storage temperature and sprout inhibitors - Mary V. Zaehringer; Helen H. Cunningham; Walter C. Sparks (American Journal of Potato Research, 1966)

Erratum - I. L. Nonnecke; W. E. Torfason; L. C. Young; P. Nandi; S. P. Raychaudhuri; Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks; Clarence J. Miller; Richard L Sawyer (American Journal of Potato Research, 1966)

Effect of storage temperature and sprout inhibitors on mealiness, sloughing, and specific gravity of Russet Burbank potatoes - Helen H. Cunningham; Mary V. Zaehringer; Walter C. Sparks (American Journal of Potato Research, 1966)

The potato — its genetic and environmental variability - F. J. Stevenson; R. V. Akeley; C. E. Cunningham (American Journal of Potato Research, 1964)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Inheritance of factors affecting potato chip color and their association with specific gravity - C. E. Cunningham; F. J. Stevenson (American Journal of Potato Research, 1963)

Minutes of Executive Committee Meeting, Annual Business Meeting, Committee reports and Financial Report - L. C. Young; Richard L. Sawyer; Hugh J. Murphy; J. W. Scannell; John C. Campbell; Walter C. Sparks; Ora Smith; William B. Raymer; R. H. Treadway; J. C. Campbell; Arthur Hawkins; R. G. Rowberry; et al. (American Journal of Potato Research, 1962)

Report of the potato utilization committee - C. E. Cunningham; O. C. Turnquist; D. R. Isleib; E. J. Wheeler; R. L. Sawyer; P. A. Xander; W. C. Sparks; R. H. Treadway (American Journal of Potato Research, 1959)

Effect of size of plot, experimental design and replication on efficiency of potato fertilizer experiments - G. L. Terman; Mildred R. Covell; C. E. Cunningham (American Journal of Potato Research, 1957)

Cooperative potato variety trials in maine - C. E. Cunningham; R. V. Akeley; K. F. Nielsen (American Journal of Potato Research, 1956)

Potato variety yields, total solids, and cooking quality as affected by date of vine killing - R. V. Akeley; F. J. Stevenson; C. E. Cunningham (American Journal of Potato Research, 1955)

Effect of date and method of kill on yield, specific gravity and other quality factors of maine potatoes - G. L. Terman; C. E. Cunningham; Michael Goven (American Journal of Potato Research, 1952)

Reducing sugar content of maine-grown potatoes treated with maleic hydrazide - M. E. Highlands; J. J. Licciardello; C. E. Cunningham (American Journal of Potato Research, 1952)

Potato vine killing methods as related to rate of kill, vascular discoloration, and virus disease spread - C. E. Cunningham; P. J. Eastman; Michael Goven (American Journal of Potato Research, 1952)

Effect of soil reaction on the performance of certain scab-resistant and susceptible potato varieties - J. H. Ellison; W. C. Jacob; H. S. Cunningham (American Journal of Potato Research, 1951)

Effect of storage temperature and size on French fry quality, shrinkage and specific gravity of Maine potatoes - G. L. Terman; Michael Goven; C. E. Cunningham (American Journal of Potato Research, 1950)